The Relationship Between Learning Methods And Student Learning Outcomes In Pastry And Bakery Products Subjects At SMK.N 9 Padang - Pepriyanti, Fanny; Elida, Elida (Universitas Negeri Padang, 2022)
This research is motivated because there are still low student learning outcomes in the Pastry and Bakery Products subjects. The purpose of this research is to describe how to learn with student learning outcomes in the subject of Pastry and Bakery Products at SMK N 9. The type of quantitative research is correlational type. The research was conducted at SMK N 9 Padang. The population is 198 students with a sample of 66 students using the Random Sampling technique. Sources of research data are students of class XII who have undergone the subject of Pastry and Bakery Products in class XI. The data collection technique used a questionnaire which was measured using a Likert scale. The data analysis technique is done by analyzing the correlation coefficient and the correlation coefficient test. The results of the study indicate that the way students learn in the Pastry and Bakery Products subject as a whole is included in the very high category with a frequency of 31 (46.96%), student learning outcomes in the Pastry and Bakery Products subject as a whole fall into the Good category with frequency of 48 (72.73%), based on hypothesis testing there is a positive and significant relationship between learning methods and student learning outcomes in the Pastry and Bakery Products subject with a significant value of 0.001.